Single-Cell Sequencing Yields Insights in the Evolution of Foot-and-Mouth Disease Virus Persistent Infection - Yuan, Yuncong; Wang, Xingran; Li, Jiadai; Han, Lingling; Du, Hang; Sun, Yidan; Yang, Pu; Zhou, Zhou; Gu, Meijia; Lu, Yang; Shen, Chao (Frontiers in Cellular and Infection Microbiology, 2022)
In order to elucidate the mechanism of cellular heterogeneity formation in FMDV persistent infection cell line. Single cell sequencing was performed on BHK-Op, and pseudo-time trajectory plot was draw through cell cluster. Based on the cell clusters, we predicted the development and progression of the FMDV persistent infection. It could be well explained by the fact that in BHK-Op cells, there are a fraction of infected cells, and a fraction of virus-exposed but uninfected bystander cells. By further comparing the transcripts in cell clusters, we found that these genes were involved in changes in ribosome biogenesis, cell cycle and intracellular signaling including the interferon signaling pathway and MAPK signaling pathway. Through comprehensive cross-tabulation analysis of differential expressed genes in various cluster of cells, we identified a high association of Fos, a transcription factor downstream of the MAPK/ERK signaling pathway, with viral replication during the formation of FMDV persistent infection. Through the further study of Fos, we found that down regulation of Fos, facilitates viral clearance during FMDV persistent infection. Upregulation of c-Raf, which are the upstream of the MAPK/ERK signaling pathway, could promote FMDV replication through down-regulation of Fos. Our research is the first to provide insight into the mechanism of the formation FMDV persistent infection through single cell sequencing using persistent infection cell line. Pseudo-time trajectory analysis was the first time to apply for FMDV persistent infection cell line. Our work highlights the detailed overview of the evolution of FMDV persistent infection. We also analyzed the differential expressed genes in the replication or elimination of FMDV within the host. We found that the MAPK/ERK signaling pathway and its downstream transcription factor Fos play an important role in FMDV persistent infection.